(untitled) - Heathcote, F. R. (Ipswich, 2001)
Basic Access 2000: Introduces pupils to the fundamentals of databases using Microsoft Access; Is suitable for whole class, group and individual teaching; Offers a gradual introduction to the correct technical vocabulary to enable ease of communication; Is divided into a series of lessons wich pupils can follow at their own pace with minimal teacher assistance; Show how to perform basic tasks such as creating tables, queries, reports, charts and form.
Keywords: Database management,Microsoft Access,Quản trị cơ sở dữ liệu